Комп’ютерне моделювання процесiв динамiчного деформування структурованого геофiзичного середовища - Даниленко, В.А.; Микуляк, С.В. (Видавничий дім "Академперіодика" НАН України, 2008)
We have carried out the computer simulation of the dynamic deformation of a discrete medium by using two models: I all discrete elements have the identical size II the medium is formed by three-size elements. We have got the diagrams of deformation of the massifs at different speeds of loading and different amplitudes, as well as those under the action of multiple loadings. The characteristic properties of all diagrams are the nonlinearity, hysteresis, and the dependence of the diagram shape on the deforming speed: if the loading duration increases, the curvature of a deformation diagram increases too, but the hysteresis area decreases. These characteristic properties of deformation diagrams are typical of such structured rocks as sandstone, limestone, and others.